Adopting net-zero supply chains: Integrated model of TOE and TAM in emerging economy context - Naveen Virmani; Pranav Kumar; Koppiahraj Karuppiah; Sandeep Jagtap (Sustainable Futures)
Industries across the globe are making arduous efforts to mitigate emissions and use greener ways of transporting goods and delivering services. The supply chain includes all the activities which involve producing, transporting, and distributing goods and services, contributing to a major portion of worldwide emissions. Road transport contributes majorly to emissions; therefore, focusing on net-zero supply chains (NZSCs) is imperative. Yet, there are several challenges in the net-zero supply chain adoption pathway. Hence, in the presented study, the Technology, Organizational, and Environment and Technology Acceptance Model integrated framework determined behavioral intentions toward adopting NZSCs. The questionnaire was developed, and 206 responses were collected. Structural Equation Modeling was used to assess the proposed research model. Various constructs analyzed under the Technology, Organizational, and Environment framework were green modes of transportation (GMT), lean green integrated digital innovations (LGDI), Management Support (MS), Organizational Competency (OC), Industry Partnership and Collaborations (IPC), and Government Rules and Regulations (GRR). Similarly, perceived usefulness (PU) and perceived ease of use (PEU) constructs were analyzed under the Technology Acceptance Model framework. Moreover, the mediation analysis of perceived usefulness and perceived ease of use constructs was analyzed between distinct constructs and intention to adopt NZSCs. Government Rules and Regulations are found to have a strong role in mitigating environmental pollution and achieving sustainable development goals. Also, green modes of transportation do not have significant relationship between perceived usefulness. Likewise, relationship between organizational culture and perceived ease of use does not hold.